Blockchain and the digital economy : the socio-economic impact of blockchain technology - Steinmetz, Fred.; Ante, Lennart; Fiedler, Ingo. (Newcastle upon Tyne : Agenda Publishing, 2020)
Blockchain technology has the potential to disrupt digital interaction in our economy and society. The technology's rapid and dynamic technical development is driven by startups and incumbents alike, creating a myriad of applications across economic and societal domains. However, the implications of this potential new technological paradigm have not yet reached wider public debate, nor have economic and societal implications been adequately explored.0Distributed ledger technologies and blockchains stem from an ideological open-source movement and facilitate the exchange of assets via a complementary technical layer on top of the internet. Current platform-based business structures like Facebook, Uber, Airbnb or Amazon could be replaced by evolving decentralized ecosystems. At the same time, community-owned neutral networks could facilitate a re-empowerment of individuals including but not limited to the sovereignty over one's data. It is likely that blockchain technology will eventually affect everyone in our society. In this book the key concepts of blockchain technology and an overview of the machinations of different blockchain ecosystems are presented. The socio-economic impact of this new technology is discussed including its impact on sectors such as energy, data, capital markets, logistics, and gambling.
Introducting blockchain -- Blockchain's basic components -- Potential and actual socio-economic impacts of blockchain -- Applications of blockchain technology in different domains -- Conclusion : possible directions of blockchain.
Includes bibliographical references (p. 179-185) and index.
Keywords: Blockchains (Databases) -- Economic aspects